The Economics of PPO Benefit Plans in Private Dental Practice - Michael Perry (Taylor & Francis Group, 2023)
ABSTRACTPrimary stakeholders in dentistry have typically been dentists and patients, but insurance companies and the employers who purchase dental benefit plans for their employees have become significant stakeholders as well. As with any industry, the marketplace is constantly evolving and the interests of stakeholders can be synergistic, but also in conflict. This article will discuss the past, present, and future relationships between private practice dentists and dental insurers. The goal is to help dentists make strategic choices for their individual practices and their professional futures.